AUGUSTINIAN MODEL IN THE BYZANTINE POLITICAL THINKING. CASE STUDY: THE ELEMENTS OF POLITICAL AUGUSTINISM IN THE CURRENT ROMANIAN MENTALITY - ANDREI TINU; CATALIN BOBOC; ANDREI-SEBASTIAN DUMITRESCU; VIOLETA IOSEFIDIS-SERGHEI (Challenges of the Knowledge Society)
The byzantine society, de jure and de facto heir of the Greco-Roman world, has it’s own philosophy, it’s own structure model and policy thinking. Without doubt, for the New Rome this model is that sprang from the Christian teachings, and as a philosophy it harmoniously blends the legacy of the Roman world with Blessed Augustine’s thinking about man and city which itself is a symbiosis between the acquired pagan knowledge and Christian experience of the latter. The Byzantine fortress (The Empire-n.n.) will use religion as the main instrument for political and social consolidation. Religion (Christianity – n.n.) is, for the Byzantine monarchy , the path to divinity, immortality... The Byzantine Christianity is not just a "phrase invented by them" as in the words of Eminescu, but a complex mechanism which represents the totality of good concepts about the world and about life of the constantinopolitan city.In preparing this study we started from the model offered by St. Augustine, "De Civitate Dei", a model which compares the two types of cities - people's city, with all its flaws, and the City of God, personified by the Church to which the Christian Roman Empire provides the Regnum. Our study tries to reflect how the model of the two cities becomes a political ideology of the Byzantine Empire and, arch over time, how it is manifested in the public and political mind of the Romanian society. This research tries to increase the understanding of the mental archetypes amongst those who are active participants in public life in Romania. However, we want our message to be disseminated in a wider public and to provide the possibility of assimilation, as much as it can, of the participatory political culture. Thus, the study becomes an attempt of reporting the Byzantine society, respectively the current Romanian society, to the model of the three types of political culture offered by Almond and Verba - participatory, parochial and dependent.